The Impact of Salesperson’s Functional and Relational Customer Orientation on Customer Outcomes - Alrajhi, Abdulaziz Saleh (Journal of Ecohumanism, 2025)
This study aims at exploring the impacts of salespeople’s functional and relational customer orientation on customer outcomes as a whole construct consisting of customer satisfaction and customer loyalty. Research data were gathered using two samples of customers of electric home appliances as customers of search products, and perfume retailing as customers of experience customers. Following a convenience sampling techniques using an electronic 5-point Likert scale, a total of 391 and 426 responses were collected from sample 1 and sample 2, respectively. Using SmartPLS software, the results indicate that both salesperson’s functional and relational behaviors had significant effects on customer outcomes. However, the functional behavior had higher effect in search products case whereas the effect of salesperson’s relational behavior is larger for experience products. This study fills a gap in the literature on such effects using local samples of customers, and its contribution is that it instructs researchers and practitioners that customer outcomes are affected by material factors such as industry type and immaterial factors such as salesperson’s behaviors.